A Study on Tobacco Cessation by Clinical Pharmacist - B J, Mahendrakumar; M, Soumya; B D, Jagadish; M, PraveenKumar; S C, Varun (Indian Journal of Pharmacy Practice)
Tobacco use is one of the major risk factor for 6 out of 8 leading causes of death in the world.It has been estimated that there are 1.1 billion smokers worldwide and 182 million (16.6%) of them live in India. It has been predicted by the World Health Organization (WHO) and tobacco consumption will become the single leading cause of death. The objective of this study was to understand and assess knowledge; characteristics towards tobacco use and conduct program to create awareness on tobacco cessation. A prospective, interventional and survey based study was conducted in and around tertiary care teaching hospital. 110 tobacco users were interviewed and enrolled. Out of 110 tobacco users, 60 registered to quit tobacco use and from among them 21(35.00%) tobacco users were counselled and given free nicotine chewing gum samples. Out of 21 subjects who were counselled, educated and motivated, 16 tobacco users reduced or quit using tobacco use. This study further supports the utilization of a clinical pharmacist within a tobacco cessation group setting. In future, the tobacco cessation program could be tailored to effectively maximize the pharmacist's time, while also achieving the best patient outcomes. Thus, in this study the clinical pharmacist intervention brought an impact on tobacco users to reduce and quit tobacco use.
Keywords: Tobacco; smoking cessation; clinical pharmacist; nicotine